Dining room management and accomodating guests [videorecording]. - Educational Foundation (National Restaurant Association). (Chicago, Ill. National Restaurant Association, 1993)
Designed to help foodservice employees in organizing the dining room, accommodating guest's needs; smokers and non-smokers; managing miscellaneous conflicts.
Keywords: Table service; Food service employees -- Training of; Food service management